Pemanfaatan Internet Diera Digital - Suffi Raihan Asfara; Wahyu Gunawan; Nurdi Nurdi (Jurnal Pendidikan Fisika dan Sains, 2019)
This study entitled "survey on the use of wi-fi among high school students in café at langsa city", a qualitative study with a constructivist approach to the use of wi-fi cafe for high school students / ma in all langsa at warung kopi pos kupi langsa , hanif kopi, z coffe, kupi micro 2, kupi mikro, kupi station, kopi ibam, wisma coffe, amico, stroom, taufik kopi, rh. The purpose of this study is to use wi-fi facilities for high school students / ma in the city of langsa. This research method uses qualitative methods, using proportional random sampling method. Keyword: Cafe, Students, Wi-Fi.